Murals make (Our) history: paintings on the wall as media of cultural memory. Interpreting the current state of Warsaw’s commemorative murals - Ilija Upalevski (Przeglad Socjologii Jakosciowej, 2017)
The aim of this paper is to closely examine the ways in which the outdoor mural as a form of art. has been used for commemorative purposes in the context of the Polish capital. Drawing on content analysis this paper will argue that regardless of their democratic potential and potential to act subversively in the public domain, the commemorative murals in the case of Warsaw are predominantly reflecting the official narrations/representations of the past and thus reproducing the state-supported, nation-centered, male-dominated perspective of history. Referring to Wulf Kansteiner methodological instructions, the paper introduces the notion of “secondary” memory makers in order to describe the position the mural makers are occupying in the field of Warsaw’s cultural memory. It will also be argued that mural makers, by adapting their works to the demands of the cultural institutions responsible for the memory production and dominant discourses of memory from mainly pragmatic reasons, are forgoing a fair portion of the democratic and subversive potential of the murals. As such, the paintings on the walls are, intentionally or not, further involved in more complex state-sponsored strategies of nationalizing the public space.